2020
DOI: 10.4314/ahs.v20i4.18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological profile of adult inpatients with community acquired pneumonia in Ilorin, North Central, Nigeria

Abstract: Background: The optimal management of community acquired pneumonia (CAP) depends on the clinical and microbio- logical profile in the locality. Objectives: To determine the clinical and microbiological profile of patients admitted with CAP in Ilorin, Nigeria. Methods: One hundred and two consenting consecutively selected patients with clinical and radiologic confirmation of CAP were recruited in 12 months. The socio-demographic, physical examination and laboratory/radiologic parameters were documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
2
1
Order By: Relevance
“…Meta-analysis results showed that the pooled prevalence of bacterial etiology of CAP among adult patients was 39.18% (36.34–42.02). This report was in line with a study conducted in Sudan 42% [ 32 ] and lower than that in Ghana, 84.5% [ 33 ] Nigeria, 69.6% and 45.2% [ 34 , 35 ], Zambia 59% [ 36 ], Egypt 50.4% [ 37 ], Saudi Arabia 46.6% [ 38 ], Pakistan 75% [ 39 ], in a different region of India, 46.3%, 52.83%, 58.8%, 83% [ [40] , [41] , [42] , [43] ], Bangladesh 61.83% [ 44 ]; a multicenter study in China, 74.4% [ 31 ]; Asian countries, 44.8% [ 11 ] Iran, 44% [ 45 ] Spain, 50.7% [ 46 ] Vietnam, 61.8% [ 47 ] and Ukraine 100% [ 48 ]. This variation may be attributed to differences in the study setting, the characteristics of the study population, and sample size.…”
Section: Discussionsupporting
confidence: 92%
“…Meta-analysis results showed that the pooled prevalence of bacterial etiology of CAP among adult patients was 39.18% (36.34–42.02). This report was in line with a study conducted in Sudan 42% [ 32 ] and lower than that in Ghana, 84.5% [ 33 ] Nigeria, 69.6% and 45.2% [ 34 , 35 ], Zambia 59% [ 36 ], Egypt 50.4% [ 37 ], Saudi Arabia 46.6% [ 38 ], Pakistan 75% [ 39 ], in a different region of India, 46.3%, 52.83%, 58.8%, 83% [ [40] , [41] , [42] , [43] ], Bangladesh 61.83% [ 44 ]; a multicenter study in China, 74.4% [ 31 ]; Asian countries, 44.8% [ 11 ] Iran, 44% [ 45 ] Spain, 50.7% [ 46 ] Vietnam, 61.8% [ 47 ] and Ukraine 100% [ 48 ]. This variation may be attributed to differences in the study setting, the characteristics of the study population, and sample size.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is comparable with a previous review reporting the pooled prevalence of bacterial pneumonia in Sudan (33.33%), and a systematic review and meta-analysis of pneumonia in east African children (34%) [ 35 ], Sudan (42%) [ 36 ], Asian countries (44.8%) [ 37 ], Iran (44%) [ 38 ] and India (46.3%) [ 39 ]. On the contrary, the finding of the present systematic review and meta-analysis is massively higher than systematic review and meta-analysis on the pooled magnitude of pneumonia among under-five children in Ethiopia which accounted 18.03 [ 40 ] and lower than the study in Ghana 84.5% [ 41 ], Nigeria 69.6% and 45.2% [ 42 , 43 ], Zambia 59% [ 44 ], Egypt 50.4% [ 45 ], Pakistan 75% (37), in different regions of India 52.83% and 58.8%, 83% [ 46 , 47 ], Bangladesh 61.83% [ 48 ], multicenter study in China 74.4% [ 49 ], Spain 50.7% [ 50 ], and Vietnam 61.8% [ 51 ]. This could be due to differences in the study setting, genetic background of the study population, and sample size.…”
Section: Discussioncontrasting
confidence: 64%
“…In contrast to Hospital acquired pneumonia (HAP) which is defined as that acquired after a minimum of 48 hours stay in the hospital, Community acquired pneumonia refers to that contracted outside the hospital setting or before 48 hours of stay in the hospital [3]. It is a leading cause of sepsis [4], accounting for an ample portion of the global infectious diseases burden, mortality and morbidity; especially in resources challenged countries [5]. The World Health Organization (WHO) estimates the annual global mortality arising from Community acquired pneumonia at between three and four million [6].…”
Section: Introductionmentioning
confidence: 99%